I'm number one - Rosen, Michael, 1946-; Graham, Bob, 1942- (Somerville, Mass. : Candlewick Press, 2009)
A wind-up soldier bosses and berates the other toys, making them feel terrible, until they suddenly start to rebel.
Kirkus Review
Publisher's Weekly
Kirkus Review, November 2009
Publisher's Weekly, November 2009
1.0
K-3.
Keywords: Human behavior -- Juvenile fiction; Self-esteem -- Juvenile fiction; Toys -- Juvenile fiction; Behavior -- Fiction; Self-esteem -- Fiction; Toys -- Fiction; Human behavior -- Fiction; Self-esteem -- Fiction; Toys -- Fiction; Picture books for children